Analysing dimensions and indicators to design energy education framework in Malaysia using the analytic hierarchy process (AHP) - Ilham, Zul; Subramaniam, Indrani; Jamaludin, Adi Ainurzaman; Wan-Mohtar, Wan Abd Al Qadr Imad; Abdul Halim-Lim, Sarina; Ohgaki, Hideaki; Ishihara, Keiichi; Abu Mansor, Mohd Radzi (Elsevier, 2022)
In order to progress towards a more sustainable energy future, Malaysia should reduce its reliance on fossil-based energy sources and shifting to green and renewable energy. Therefore, focus on energy education awareness programmes emphasising sustainable behaviours and frameworks are required. These programmes connect with Sustainable Development Goal 7 of the United Nations, which is to provide affordable and clean energy. In this study, dimensions and indicators of a framework for energy education were studied and evaluated in an effort to improve decision making. This study systematic approach comprised a review of relevant literature and consultation with an ad hoc panel of energy education experts via surveys, interviews, and questionnaires. This study also included an analytic hierarchy process to evaluate the framework’s criteria selection, alternative indicators, and priority or weights. The results indicated that the “Aim to minimise climate change” dimension is deemed the most essential criterion for selecting energy education dimension criteria. On the other hand, “National policy makers” is the most essential stakeholder across all parties. It has been determined that the use of analytic hierarchy process to the design of the framework for energy education in Malaysia could help simplifies a systematic decision-making process.